Frequency agile multiple‐input‐multiple‐output antenna design for 5G dynamic spectrum sharing in cognitive radio networks. Issue 3 (24th September 2020) - Hussain, Rifaqat; Khan, Muhammad U.; Iqbal, Naveed; AlMajali, Eqab; Alja'Afreh, Saqer S.; Johar, Umar; Shamim, Atif; Sharawi, Mohammad S.
Abstract: In this work, 2‐element slot‐based frequency reconfigurable (FR) multiple‐input‐multiple‐output (MIMO) antenna design antenna with a very wide‐sweep is proposed for dynamic spectrum sharing (DSS) in 5G technologies. FR is achieved using varactor diode with frequency tuning range from 1655 to 2605 MHz. The design is a low profile with planar structure having a single element footprint of 19.5 × 20 mm 2 . The two slot antenna elements of the MIMO configuration are etched out from a ground (GND) plane of dimensions of 60 × 120 mm 2 . The proposed antenna is narrow‐band and hence it is suitable for RF front‐end in the 5G‐enabled DSS in cognitive radio (CR) applications.